Cow’s milk allergic patients should be informed of the sources of caseinate - Kocabaş, Can Naci; Sekerel, Bülent Enis (The Turkish Journal of Pediatrics, 2003)
Cow’s milk allergy is one of the most common food allergies prevalent during infancy and it may cause anaphylactic reactions in more sensitive patients. Cow’s milk is found in a large variety of processed foods but its presence may be hidden as it is occasionally listed on the product label in an manner unrecognizable to the consumer. The parents of more sensitive patients need to be instructed in the detection of these potential sources of hidden cow’s milk by judiciously reading food labels and in recognition of the sources, thus avoiding possible untoward reactions. We report a patient with cow’s milk allergy who had an anaphylactic reaction following the ingestion of a hot dog product that contained caseinate. The label of the ingested hot dog product listed only the code number of caseinate. Avoidance of such occurrences would be more likely if firstly food products were labeled more accurately and secondly if physicians were to instruct their patients more thoroughly about their allergies, including the relevant names of all allergens.